Pengaruh Content Marketing dan Brand Awareness dalam meningkatkan Minat Beli para Pengguna Aplikasi TikTok (Studi Kasus Minat Beli Pengguna Aplikasi Tiktokshop di Daerah Cikarang) - Pangesti, Puji Tri; M Mustaqim (TALI JAGAD JOURNAL, 2025)
The purpose of this study was to see how content advertising and brand awareness affect the purchase intention of TikTok Shop application users in the Cikarang area. The development of digital technology and social media trends have encouraged business actors to use platforms such as TikTok for their advertisements. There is a belief that interesting marketing content and high levels of brand awareness have the ability to create positive perceptions and increase customer purchase intention. This study uses a quantitative approach and surveys as its instruments. Ninety-one people surveyed were active TikTok users in Cikarang. To find out how much influence each independent variable has on the dependent variable, the multiple linear regression data analysis method was used. The results of the study show that brand knowledge and content marketing have a positive and significant impact on customer interest in purchasing goods on the TikTok Shop application. This shows how important content strategy and brand strengthening are to attract customers' attention and encourage them to purchase goods at social media-based online stores such as TikTok Shop.